Os estágios supervisionados do curso de pedagogia da Universidade Federal do Maranhão - Buzar, Solange Silva (1982)
The objective of this work ~s to analyze the legally proclaimed function of the Supervised Training in the Pedagogy Course of the Federal University of Maranhão - UFMA. Aiming at this purpose we tried to estudy the function of the training related to the widest social contexto Thus, a historical flashback had to be made on the University of Maranhão since it is not possible to isolate the relation part/whole. Lo oking f orwar d to und er s t andi ng th i s phenomenon inside its concret wholeness,we choose the surveyandanalysis of empiric data about the reality of Supervised Training concerning the following qualifications included ~n the Pedagogy Course of UFMA -- School Administration,Supervision, Inspection, Educational Orientation and Teaching. S uch ana ly si s showed tha t the Supervised Training does not represent in fact, the link betwen theoretical knowledge and concrete, practical work; the contents of theoretical subjects during the Pedagogy Course in UFMA do not serve as a basis and support for the praxis of the Training; the practical part of the Training has a merely utilitarian character. Considering all these aspects, we came to the conclusion that the Supervised Training of UFMA Pedagogy Course, under every . theoretical approach, must be reviewed. The following suggestion is made: that a new Integrated Supervised Training be created, covering all five areas, School Administration, Supervising, Inspection, Educational Orientation and Teaching, aiming at seizing the school reality as a whole by means of a procedure that simultaneously inserts and integrates the elements which act in the school organization. This Inte g rated Supervised Training shall be developed in three steps or rnornents: classroorn observation, study of the school structure and running; elaboration and application of alternative proposals.